Roles of serum and biliary CEA, CA19-9, VEGFR3, and TAC in differentiating between malignant and benign biliary obstructions - İnce, Ali Tüzün and Yıldız, Kemal and Baysal, Birol and Danalıoğlu, Ahmet and Kocaman, Orhan and Tozlu, Mukaddes and Gangarapu, Venkatanarayana and Sarbay Kemik, Ahu and Uysal, Ömer and Şentürk, Hakan (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Despite the presence of many diagnostic methods, the differential diagnosis between benign and malignant biliary obstructions is still not easy. We aimed to evaluate the role of serum/biliary carcinoembryonic antigen (CEA), carbohydrate antigen 19-9 (CA 19-9), vascular endothelial growth factor receptor-3(VEGFR-3), and total antioxidant capacity (TAC) tests in this differential diagnosis. Materials and Methods: Patients (n:225; 110♂, 115♀) with diagnosis of malignant (n:96) or benign (n:129) biliary obstruction were included in this cross-sectional study. Serum and biliary CEA, CA 19-9, VEGFR-3, and TAC tests were analyzed, statistics were obtained, and significance was defined as p<0.05. Results: Mean age was 54.9±16.4 for the benign and 54.2±19.6 for the malignant group (p=0.89). Head of pancreas cancer (18.2%), cholangiocarcinoma (11.4%) and choledochal stone (48%) were the most common etiologies. The area under the curve (AUC)s by ROC analysis of serum/biliary CA 19-9, VEGFR-3, and TAC and serum CEA were 0.701/0.616, 0.622/0.663, 0.602/0.581, and 0713, respectively. Serum TAC had higher sensitivity (61.1%) and CEA had lower sensitivity (42.7%), whereas CEA had higher specificity (89.9%) and TAC had lower specificity (60.5%). In biliary tumor markers, CA 19-9 had higher sensitivity (74%) and VEGFR-3 had lower sensitivity (56.2%); however, VEGFR-3 had higher specificity (79.1%) and CA 19-9 had lower specificity (34.1%). Additionally, combination of serum CEA (p<0.001), CA 19-9 (p<0.001), VEGFR-3 (p<0.001), and biliary CA 19-9 (p=0.028) markers achieved 95% estimation probability, and the sensitivity, specificity, and accuracy were 88.5%, 45.7%, and 64%, respectively. Conclusion: Serum and biliary CEA, CA 19-9, VEGFR-3, and TAC tests would not be useful in the differentiation between malignant and benign biliary obstructions.